2022
DOI: 10.1177/00033197221114689
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Antibiotic Use During Insertion of Cardiovascular Implantable Devices Among United States Implanters

Abstract: Antibiotic use for cardiovascular implantable devices (CIED) prophylaxis is well-accepted despite a paucity of data. Pre-procedural prophylaxis lowers the rate of CIED infections; however, data is lacking for intra- or post-procedural antibiotic use. Antibiotic-eluting envelopes (ENVELOPE) [TYRX®TM] have been shown to reduce post-procedural infections. Understanding implanter practices may provide insight as to the need for antibiotic stewardship. The purpose of this survey was to assess the practices of impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
2
0
0
Order By: Relevance
“…Finally, we looked closely at preoperative antibiotic prophylaxis compliance (which similar to the WRAP-IT trial was not controlled in our study) in conjunction with envelope usage, which revealed diverse and some concerning practice patterns. This finding is also corroborated by a recent independent survey of implanting physicians in the USA, which is further described below ( 39 ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Finally, we looked closely at preoperative antibiotic prophylaxis compliance (which similar to the WRAP-IT trial was not controlled in our study) in conjunction with envelope usage, which revealed diverse and some concerning practice patterns. This finding is also corroborated by a recent independent survey of implanting physicians in the USA, which is further described below ( 39 ).…”
Section: Discussionsupporting
confidence: 80%
“…Our findings are similar to recently published results from an independent survey of antibiotic use during CIED implantation in the United States. Although the survey respondents reported a 97% rate of routine use of pre-operative systemic antibiotics (similar to our 96.6% overall compliance rate), the authors also found that there were wide variations in implanter practices ( 39 ).…”
Section: Discussionsupporting
confidence: 80%